In healthy primates, circulating autoreactive T cells mediate autoimmune disease. - Genain, C P (1994)
A T cell response against myelin basic protein (MBP) is thought to contribute to the central nervous system (CNS) inflammation that occurs in the human demyelinating disease multiple sclerosis. To test whether MBP-reactive T cells that are normally retrieved from the circulation are capable of inducing CNS disease, MBP-reactive T cell clones were isolated from the peripheral blood of healthy, unimmunized Callithrix jacchus (C. jacchus) marmosets. This primate species is characterized by a natural chimerism of bone marrow elements between siblings that should make possible adoptive transfer of MBP-reactive T cells. We report that MBP-reactive T cell clones efficiently and reproducibly transfer CNS inflammatory disease between members of C. jacchus chimeric sets. The demyelination that is characteristic of experimental allergic encephalomyelitis induced in C. jacchus by immunization against human white matter did not occur after adoptive transfer of the MBP-reactive clones. It was noteworthy that encephalitogenic T cell clones were diverse in terms of their recognition of different epitopes of MBP, distinguishing the response in C. jacchus from that in some inbred rodents in which restricted recognition of MBP occurs. These findings are the first direct evidence that natural populations of circulating T cells directed against a CNS antigen can mediate an inflammatory autoimmune disease.